1995
DOI: 10.1111/j.1460-2695.1995.tb00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Closure Behaviour of Fatigue Cracks in Residual Stress Fields

Abstract: An elastic-plastic finite element analysis with high order elements is performed to examine closure behaviour of fatigue. cracks in residua1 stress fieids and the numerical results are then compared with experimental results. The finite element analysis, performed under plane stress using 8-node isoparametric elements, can predict fatigue crack closure behaviour through residual stress fields very well. The crack opening and closing behaviour through a compressive residual stress field is found to be complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…It has been reported by McClung and Sehitoglu [8,9] and Choi and Song [7] that the crack opening level under plane stress is higher than under plane strain and that the plane stress crack opening data agree closely with the experimental results. The analysis is performed only under plane stress in this study.…”
Section: A Two-dimensional Finite Element Modelsupporting
confidence: 84%
See 1 more Smart Citation
“…It has been reported by McClung and Sehitoglu [8,9] and Choi and Song [7] that the crack opening level under plane stress is higher than under plane strain and that the plane stress crack opening data agree closely with the experimental results. The analysis is performed only under plane stress in this study.…”
Section: A Two-dimensional Finite Element Modelsupporting
confidence: 84%
“…In particular, the finite element (FE) numerical method has long been used and has provided useful results of fatigue crack growth and closure behaviour under variable loading [3-61. Quite recently, it is reported that the closure behaviour of fatigue cracks in residual stress fields can be successfully analyzed by the FE method [7].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the studies of Choi andSong (1995) , Park et al (1997) and , the crack growth phenomenon through the numerical analysis is simulated as releasing a node along crack line when a nodal reaction force change from tension to compression force. The valid crack opening level is obtained when it becomes stable after the crack tip advances beyond the monotonic plastic zone induced by the initial crack length.…”
Section: Plastic Zone Of Fatigue Crackmentioning
confidence: 99%
“…Therefore, the finite element method to precisely predict the behavior of fatigue crack closure is essential. Recently the crack closure behavior at the residual stress fields was successfully studied (Choi and Song, 1995) and special attention was given to the determination of the most appropriate mesh size that would provide good numerical results (Park et al, 1997). Park et al, (1997) reported that a unique and most-appropriate mesh size exists for a given loading condition that would provide good A comparison between numerical and experimental results is very important to derive quantitative conclusions from finite element method.…”
Section: Introductionmentioning
confidence: 99%
“…07-0120) [DOI: 10.1299/jmmp. 1.719] the closure behavior of fatigue crack (1) ; with special device of ultrasonic, the crack tip progress is detected (2) ; with aiming at local conditions of crack tip, the effects of grain orientation are investigated (3) ; and with analytical approach, the prediction of crack growth rate is tried on to give an insight into crack development (4), (5), (6) In the study, aiming to clarify the practical crack tip behavior, at first, the estimate expression was inferred by developing the Irwin's model under supposition of a small scale of yielding and considering the effect of cycle frequency for predicting crack tip opening displacement. And then, the crack growth rate was computed.…”
Section: Introductionmentioning
confidence: 99%